PRIORITIES OF NATIONAL OIL AND GAS STRATEGY OF THE COUNTRIES OF THE CASPIAN REGION - D. Kuramshin (Вестник университета)
In the recent years problems of energy cooperation of the countries of the Caspian region were staticized, as its countries aim at implementation of own independent strategy of export of hydrocarbons. The article is devoted to an assessment of the main directions of development of energy strategy of the countries of the Caspian region in the modern conditions of globalization of world power.